Phytochemical Screening and Antioxidant Activity of Coronilla valentina - Gambo, Bulus Godiya; Mercy, Magomya Asabe; Ifeoma, Iyen Sandra (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
This study investigated the phytochemical constituents and antioxidant activity of Coronilla valentina. The leaves and stems of the plant were air-dried, powdered, and extracted using hexane, ethyl acetate, acetone, and methanol. Phytochemical analysis revealed the presence of tannins, phenols, flavonoids, terpenoids, and alkaloids in both leaf and stem extracts. The quantitative analysis of phytochemicals in the crude extracts of Coronilla valentina revealed notable concentrations in both leaves and stems. In the leaf extract, phenols were found to be the most abundant at 2.43 mg/g, followed by alkaloids at 2.23 mg/g, flavonoids at 2.21 mg/g and saponins at 0.43 mg/g. Conversely, the stem extract exhibited a different pattern, with tannins being the most abundant at 2.54 mg/g, followed by phenols at 2.10 mg/g, alkaloids at 1.70 mg/g, flavonoids at 1.14 mg/g and saponins at 0.33 mg/g, respectively. The antioxidant activity of the extract was assessed using the DPPH free radical scavenging assay across concentrations from 0.0313 to 0.500 mg/mL, with ascorbic acid as the standard. Absorbance readings for the leaf and stem extracts decreased with increasing concentrations, whereas percentage inhibition increased, indicating enhanced antioxidant activity at higher concentrations when compared to the standard. Methanol extracts of both the leaf and stem demonstrated higher radical scavenging activity with percentage inhibition of 64.76% and 71.64% respectively. Among the tested extract of both the leaf and the stem, methanol and ethyl acetate extracts exhibited lower IC50 value demonstrating stronger DPPH radical scavenging activity with an IC50 value of 0.069 and 0.068 ug/mL, which is comparable to the standard with an IC50 0f 0.069 mg/mL. while hexane extracts of both the leaf and stem revealed higher IC50 value with an IC50 value of 0.29 and 0.17 ug/mL indicating weak antioxidant activity. Our findings in this study support the potential use of Coronilla valentina as a source of natural antioxidants.